Stereotactic Body Radiation Therapy for Locally Progressive and Recurrent Pancreatic Cancer after Prior Radiation - Sutera, Philip; Bernard, Mark E.; Wang, Hong; Bahary, Nathan; Burton, Steven; Zeh, Herbert; Heron, Dwight E. (Frontiers in Oncology, 2018)
Introduction Pancreatic adenocarcinoma is an aggressive malignancy that has consistently demonstrated poor outcomes despite aggressive treatments. Despite multimodal treatment, local disease progression and local recurrence are common. Management of recurrent or progressive pancreatic carcinomas proves a further challenge. In patients previously treated with radiation therapy, stereotactic body radiation therapy (SBRT) is a promising modality capable of delivering high dose to the tumor while limiting dose to critical structures. We aimed to determine the feasibility and tolerability of SBRT for recurrent or locally-progressive pancreatic cancer in patients previously treated with external beam radiation therapy (EBRT). Materials and Methods Patients treated with EBRT who developed recurrent or locally-progressive Pancreatic ductal adenocarcinoma (PDAC) treated with SBRT reirradiation at our institution, from 2004-2014 were reviewed. Our primary endpoints included overall survival (OS), local control, regional control and late grade 3+ radiation toxicity. Endpoints were analyzed with the Kaplan-Meier method. The association of these survival endpoints with risk factors was studied with univariate Cox proportional hazards models. Results We identified 38 patients with recurrent/progressive pancreatic cancer treated with SBRT following prior radiation therapy. Prior radiation was delivered to a median dose of 50.4 Gy in 28 fractions. SBRT was delivered to a median dose of 24.5 Gy in 1-3 fractions. Surgical resection was performed on 55.3% of all patients. Within a median follow up of 24.4 months (IQR, 14.9-32.7 months), the median overall survival from diagnosis for the entire cohort was 26.6 (95% CI: 20.3-29.8) months with 2-year OS of 53.0%. Median survival from SBRT was 9.7 months (95% CI, 5.5-13.8). The 2-year freedom from local progression and regional progression was 58% and 82%, respectively. For the entire cohort, 18.4% and 10.5% experienced late grade 2+ and grade 3+ toxicity, respectively. Conclusion This single institution retrospective review identified SBRT reirradiation to be a feasible and tolerable treatment strategy for patients with previously-irradiated locally progressive or recurrent pancreatic adenocarcinoma.